Penalaran Moral, Kepercayaan, Keadilan Organisasi dan Intensi Whistleblowing - Felicia Fedrica; Anis Chariri (Diponegoro Journal of Accounting, 2021)
ABSTRACTThis research aimed to analyze the determinants of whistleblowing intention. Dependent variable is whistleblowing intention and independent variables are moral reasoning, trust, and organizational justice.Research data used are primary data collected by distributing questionnaires to 87 respondents who work as financial staff at BRI and Bank Mandiri in Semarang as samples. The sample selection was based on convenience sampling. Furthermore, test of the hypotheses carried out through multiple regression analysis using SPSS 25 software.The results of this study show that trust has a significant effect on whistleblowing intention, however moral reasoning and organizational justice do not have a significant effect on whistleblowing intention.